2004
DOI: 10.1073/pnas.0406196101
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Af4 protein function in the cerebellum by Siah proteins

Abstract: We have established that the gene AF4, which had long been recognized as disrupted in childhood leukemia, also plays a role in the CNS. Af4 is mutated in the robotic mouse that is characterized by ataxia and Purkinje cell loss. To determine the molecular basis of this mutation, we carried out a yeast two-hybrid screen and show that Af4 binds the E3 ubiquitin ligases Drosophila seven in absentia (sina) homologues (Siah)-1a and Siah-2 in the brain. Siah-1a and Af4 are expressed in Purkinje cells and colocalize i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 31 publications
6
47
0
1
Order By: Relevance
“…Interestingly, AF4 interacts with the E3 ubiquitin ligase SIAH1 and the minimal interaction domain of AF4 to bind to SIAH1 was demonstrated to possess the PXAXVXP motif conserved within AF5q31 and other family genes (6,57). A missense mutation V294A in the robotic mice corresponds to Val of the PXAXVXP motif, and the Val mutation of the AF4 protein has been shown to reduce the binding ability to SIAH1 protein significantly, suggesting that the phenotype of the robotic mice is caused by an increased steady-state level of AF4 protein and that all the members of the AF5q31 family are regulated by this interaction (57). Since mutation of the AF4 gene in the robotic mice occurred upstream of known translocation breakpoints, it is possible that MLL-AF4 may be more stable than AF4.…”
mentioning
confidence: 99%
“…Interestingly, AF4 interacts with the E3 ubiquitin ligase SIAH1 and the minimal interaction domain of AF4 to bind to SIAH1 was demonstrated to possess the PXAXVXP motif conserved within AF5q31 and other family genes (6,57). A missense mutation V294A in the robotic mice corresponds to Val of the PXAXVXP motif, and the Val mutation of the AF4 protein has been shown to reduce the binding ability to SIAH1 protein significantly, suggesting that the phenotype of the robotic mice is caused by an increased steady-state level of AF4 protein and that all the members of the AF5q31 family are regulated by this interaction (57). Since mutation of the AF4 gene in the robotic mice occurred upstream of known translocation breakpoints, it is possible that MLL-AF4 may be more stable than AF4.…”
mentioning
confidence: 99%
“…The robotic mutation disrupts the binding of AF4 to SIAH ubiquitin ligases, resulting in a marked decrease in proteasomal turnover of the mutant protein (Oliver et al, 2004). In the cerebellum Af4 is specifically expressed in PCs (Isaacs et al, 2003), and we have demonstrated that accumulation of robotic AF4 and colocalization of known transcriptional complex components occur in these cells (Bitoun et al, 2007).…”
Section: Introductionmentioning
confidence: 84%
“…3). Presumably because of the post-translational regulation of AF4 by the proteasome (Oliver et al, 2004), peak expression of the wild-type protein was observed at P21, 1 week later than that of transcripts ( Fig. 1).…”
Section: Accumulation Of Af4 Protein Causes Irreversible Pc Dysfunctimentioning
confidence: 99%
“…AF4 has several putative functional domains including the ALF (AF4/LAF4/FMR2 homology) domain, which mediates the interaction with a family of ubiquitin ligases called SIAH (seven in absentia homolog), a serine/proline-rich transcriptional activation domain (TAD), nuclear localization signals (NLS), a guanosine triphosphate (GTP) binding motif (GBM), and a C-terminal homology domain involved in intra-nuclear localization and binding to pre-mRNA splicing factors (Bensaid et al, 2009;Chen et al, 1993;Isnard et al, 2000;Melko et al;Morrissey et al, 1993;Oliver et al, 2004) ( Figure 5). AF4 is located at a fragile break-point region on chromosome 4 and is associated with a wide variety of chromosomal translocations.…”
Section: Domain Architecture and The Functional Roles Of Af4 Familymentioning
confidence: 99%